Accessibility of buildings and houses for disabled persons: The law and practice in Malaysia - Sufian, Azlinor (International Islamic University Malaysia, 2007)
Malaysia is one of the signatories to the proclamations of Asia & Pacific Decade of Disabled Persons (1993-2002), yet Malaysia is still lacking of comprehensive laws as regards to rights of persons with disabilities. The only law available is the Uniform Building (Amendment) By Laws, 1991(UBBL Amendment 1991) that provides for building requirements for disabled persons. This by law may be regarded as an initial step taken by Malaysia to ensure a disabled person's right to full participation in social development. Despite the existence of this by law, most buildings in Malaysia do not have proper facilities or provide easy access for persons with disabilities. Similarly as far as housing is concerned there is no statutory requirement stipulating that housing (in particular public housing) should be designed to accommodate the needs of persons with disabilities. It is the aim of this article to look into some legal provisions related to barrier free buildings including housing in Malaysia.